PENERAPAN EVIDENCE BASED NURSING TERAPI BERMAIN DOKTER-DOKTERAN (MEDICAL PLAY) UNTUK MENGATASI KECEMASAN AKIBAT HOSPITALISASI PADA ANAK PRASEKOLAH - Pricilia Dewi Sulistyawati (2023)
Anxiety is an emotional disorder that can be characterized by constant fear or worry. Anxiety can interfere with a child's development and quality of life in a child. Anxiety due to hospitalization causes stressors for children which will also cause the treatment process to be disrupted. The purpose of writing this scientific paper is to provide an overview of nursing care for preschool-age pediatric patients who experience anxiety due to hospitalization and the influence of medical play therapy innovation interventions to overcome the anxiety of preschool-age children at RSUD Pasar Minggu. Medical play therapy has the benefit of reducing the level of anxiety and fear that children experience every time a nurse or doctor performs medical action so that they get used to these tools. The number of respondents involved in this study amounted to 2 people given the intervention. Measurement of anxiety scores using the Hamilton Anxiety Rating Scale (HARS) questionnaire in family-assisted patients. Medical play therapy is done once a day for 15-20 minutes along with drug administration. Implementation carried out for 3 days and getting anxiety scores on the first day 29 (severe anxiety) and on the third day dropped to 19 (mild anxiety) which showed the effect of medical play therapy on decreasing anxiety scores of preschool-age children.